2018
DOI: 10.1097/iop.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Neovascularization Secondary to Intense Pulsed Light Injury

Abstract: The authors report a 26-year-old medical device saleswoman developing choroidal neovascularization after injury by intense pulsed light with detection and monitoring by optical coherence tomography angiography and treatment with intravitreal injection of ranibizumab. This is the first intense pulsed light-related choroidal neovascularization case, which reminds the importance of using appropriate eye protection throughout the course of treatment for all individuals present in the therapy room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“… Chang et el. (2018) 15 The anterior segment was silent. During the fundus examination, a juxtafoveal creamy patch was observed in the right eye.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Chang et el. (2018) 15 The anterior segment was silent. During the fundus examination, a juxtafoveal creamy patch was observed in the right eye.…”
Section: Resultsmentioning
confidence: 99%
“… 22 Three patients reported that they directly looked at the IPL probe while it was fired up. 15 , 24 , 27 Eighteen patients (90%) received facial IPL treatment, and 17 of their procedures were performed in a periocular location. Of those reported laser parameters, the fluence used was in the range of 20–24 J/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few complications have been published. Rare cases of uveitis [ 33 ] and one case of choroidal neo-vascularization [ 34 ] have been reported. This shows the importance of wearing protective glasses during the procedure [ 35 ] and the need to strictly position the shots on the cheekbone under the lower eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…Xu K et al [ 8 ] reported a 12-year-old boy and Tofolean IT et al [ 14 ] reported a 31-year-old woman whose BCVA improved to 20/20 after only 1 anti-VEGF injection while another 33-year-old patient [ 15 ] regained 20/20 after 3 intravitreal injections. Besides, the study groups of Tran K, [ 7 ] Forshaw TRJ, [ 16 ] Chang CY [ 17 ] and Veronese C [ 18 ] reported either complete resolution of CNV or visual improvement in young patients (aged between 12 and 26 years old). It appears that anti-VEGF treatment is quite useful for young patients who suffer from laser induced CNV.…”
Section: Discussionmentioning
confidence: 99%